2016
DOI: 10.1164/rccm.201511-2216oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protease–Epithelial Sodium Channel Signaling Improves Mucociliary Function in Cystic Fibrosis Airways

Abstract: QUB-TL1 corrects aberrant CAP activities, providing a mechanism to delay or prevent the development of CF lung disease in a manner independent of CF transmembrane conductance regulator mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 57 publications
(30 reference statements)
3
56
0
Order By: Relevance
“…6). Although “ENaC-targeting concept” is about to be confirmed by the recent basic report51 and the clinical study for the treatment of CF on a long-acting inhaled ENaC inhibitor, P1037 (VX371) (Phase 2 CLEAN-CF), beneficial effects of ONO-3403 on C57/BL6J-βENaC-Tg mice may be exerted by ENaC-independent unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…6). Although “ENaC-targeting concept” is about to be confirmed by the recent basic report51 and the clinical study for the treatment of CF on a long-acting inhaled ENaC inhibitor, P1037 (VX371) (Phase 2 CLEAN-CF), beneficial effects of ONO-3403 on C57/BL6J-βENaC-Tg mice may be exerted by ENaC-independent unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…QUB-TL1 is a potent CAP inhibitor, which has been shown to diminish ENaC-mediation sodium absorption [74]. reclinical studies of QUB-TL1 in airway epithelial cell culture demonstrated that QUB-TL1 inhibits prostasin, matriptase, and furin.…”
Section: Enac Inhibitors In Developmentmentioning
confidence: 99%
“…The cystic fibrosis transmembrane conductance regulator (CFTR) is a multi-domain, cell surface membrane glycoprotein that acts as a chloride channel [Tazi et al, 2016]. CFTR can regulate the epithelial sodium channel [Reihill et al, 2016], plasma membrane recycling [Bomberger et al, 2014], and plays a significant role in the regulation of ER stress responses [Bartoszewski et al, 2008]. Pratic o AD have previously reported that mutations of the CFTR genotype: F508/ 12TG-5T and 470MV correlate with liver disease of cystic fibrosis patients, suggesting that CFTR might be involved in liver damage [Pratico et al, 2015].…”
mentioning
confidence: 99%